«The Easter World» of Nicholas II during the Bell for Witte Tolled - Nelly Mikhailovna Tairova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
For Russia the beginning of 1905 consisted of those political events which have led further to weakening of autocracy: January 9, murder of the Grand duke Sergey Aleksandrovich, February discussions of the government, defeat of the Russian army near Mukden, Treaty of Bjorko. However S.Yu. Witte suggested Nicholas II to change system of public administration, for strengthening, hoping for Nicholas II’s prudence. But he was suspected of insincerity, the right forces created against him collusions, trying to compromise him in the opinion of the public and the tsar. At this S.Yu. Witte showed the commitment to the Russian policy and fidelity to autocracy for what has been built in count advantage.